Dispersed lipid liquid crystalline phases stabilized by a hydrophobically modified cellulose - Almgren, Mats; Borné, Johanna; Feitosa, Eloi [UNESP]; Khan, Ali; Lindman, Björn (American Chemical Society (ACS), 2007)
Aqueous dispersions of monoolein (MO) with a commercial hydrophobically modified ethyl hydroxyethyl cellulose ether (HMEHEC) have been investigated with respect to the morphologies of the liquid crystalline nanoparticles. Only very low proportions of HMEHEC are accepted in the cubic and lamellar phases of the monoolein-water system. Due to the broad variation of composition and size of the commercial polymer, no other single-phase regions were found in the quasi-ternary system. Interactions of MO with different fractions of the HMEHEC sample induced the formation of lamellar and reversed hexagonal phases, identified from SAXD, polarization microscopy, and cryogenic TEM examinations. In excess water (more than 90 wt %) coarse dispersions are formed more or less spontaneously, containing particles of cubic phase from a size visible by the naked eye to small particles observed by cryoTEM. At high polymer/MO ratios, vesicles were frequently observed, often oligo-lamellar with inter-lamellar connections. After homogenization of the coarse dispersions in a microfluidizer, the large particles disappeared, apparently replaced by smaller cubic particles, often with vesicular attachments on the surfaces, and by vesicles or vesicular particles with a disordered interior. At the largest polymer contents no proper cubic particles were found directly after homogenization but mainly single-walled defected vesicles with a peculiar edgy appearance. During storage for 2 weeks, the dispersed particles changed toward more well-shaped cubic particles, even in dispersions with the highest polymer contents. In some of the samples with low polymer/MO ratio, dispersed particles of the reversed hexagonal type were found. A few of the homogenized samples were freeze-dried and rehydrated. Particles of essentially the same types, but with a less well-developed cubic character, were found after this treatment. © 2007 American Chemical Society.
Keywords: Dispersed particles; Polymer/MO ratio; Single-walled defected vesicles; Cellulose; Hydrophobicity; Lamellar structures; Transmission electron microscopy; Liquid crystal polymers; acylglycerol; cellulose; drug derivative; ethyl 2 hydroxyethylcellulose; ethyl-2-hydroxyethylcellulose; glycerol oleate; polymer; unclassified drug; water; chemical model; chemistry; conformation; cryoelectron microscopy; crystallization; liquid crystal; methodology; particle size; physical chemistry; temperature; transmission electron microscopy; Chemistry, Physical; Cryoelectron Microscopy; Crystallization; Glycerides; Liquid Crystals; Microscopy, Electron, Transmission; Models, Chemical; Molecular Conformation; Particle Size; Polymers; Temperature; Water; Transmission Electron Microscopy; Water Repellence